Effects of Lactobacillus plantarum on Silage Fermentation and Bacterial Community of Three Tropical Forages - Liu, Yue; Chen, Ting; Sun, Rong; Zi, Xuejuan; Li, Mao (Frontiers in Animal Science, 2022)
The fermentation quality and microbial diversity of king grass (K), cassava foliage (C), Broussonetia papyrifera (B) ensiled in the absence of inoculant (K, C, B), or the presence of Lactobacillus plantarum (KL, CL, BL) for 60d were investigated. The bacterial community was characterized by using the 16S rDNA sequencing technology. The relative abundance of Lactobacillus in K was very high, and it decreased after adding L. plantarum while Acinetobacter increased to some extent. The relative abundance of Lactobacillus in group C was also very high. And the inoculant L. plantarum enriched it in CL group. As the second dominant genus of group C, the relative abundance of Pseudomonas decreased significantly in CL. Weissella and Enterobacter were the dominant genus in B and BL, and the relative abundance of Lactobacillus decreased in BL. For K, C and B, the inoculant L. plantarum decreased the pH value and NH3-N content markedly, inhibited the production of butyric acid, increased the content of lactic acid and significantly improved the fermentation quality. In conclusion, L. plantarum affected the bacterial community of C and improved the silage quality of K, C and B to a certain extent.